1995
DOI: 10.2307/3432325
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cancer Incidence, Mortality, and Survival between African Americans and Whites

Abstract: This report highlights selected evidence of different cancer patterns among African Americans and whites and considers potential risk factors associated with these cancers. During the years 1987 to 1991, African Americans experienced higher incidence and mortality rates than whites for multiple myeloma and for cancers of the oropharynx, colorectum, lung and bronchus, cervix, and prostate. African Americans had lower incidence and mortality for cancer of the urinary bladder. The incidence of breast cancer was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Recent studies have demonstrated ethnic differences in survival rates of patients with lung, endometrial, and cervical carcinoma 1,6,8,[11][12][13][14][15][16] Most of these studies attribute this difference in survival rate to the greater percentage of AAs presenting at an advanced stage, having poor socioeconomic status with impediments to care. 1,6,8,[11][12][13][14] Other studies suggest an intrinsic genetic or social factor that may adversely affect cancer survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated ethnic differences in survival rates of patients with lung, endometrial, and cervical carcinoma 1,6,8,[11][12][13][14][15][16] Most of these studies attribute this difference in survival rate to the greater percentage of AAs presenting at an advanced stage, having poor socioeconomic status with impediments to care. 1,6,8,[11][12][13][14] Other studies suggest an intrinsic genetic or social factor that may adversely affect cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…This study contains sufficient power to detect any differences in survival that have been reported previously. 6,[15][16][17] Of note, a difference in survival rate was identified when Caucasians were compared with all minorities. Most of the non-AA minority patients with advanced stage disease (60%) that came from the Army Medical Center in Hawaii account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…2 Epidemiological 3 and controlled feeding 4 studies have reported lower folate status in African American relative to Caucasian women. African American women also have a higher incidence and/or mortality rate from chronic diseases [5][6][7][8] and experience more adverse birth outcomes 9 than Caucasian women. This may be due to environmental (i.e., access to health care and nutrition) and biological factors (i.e., common genetic polymorphisms and epigenetic modifications).…”
Section: Introductionmentioning
confidence: 99%
“…The higher incidence of head and neck cancer among blacks has been attributed to a variety of factors, including differences in diet, alcoholic beverages, and tobacco use. Head and neck cancer occurs more frequently in men than in women (1,2).…”
mentioning
confidence: 99%